Treatment of fractures with plate osteosynthesis with bioactive coating - V. P. Popov; T. V. Druzhinina; Ya. A. Kamenchuk; V. D. Zavadovskaya; O. E. Akbasheva (Acta Biomedica Scientifica, 2013)
The aim. of the work was to introduce implants with bioactive coating in the practice of treatment of long tubular bones and. to assess speed of consolidation in comparison with bioinert constructions with use of clinical data, radiation and biochemical methods of examination. Use of bioactive calcium-phosphate coatings obtained by the method of microarc oxidation for the osteosynthesis of long tubular bones is accompanied by more effective consolidation of fracture area in comparison with titanium plates. In 4 months after the operation with use of bioactive implants 95,2 % of patients had. active formation and. formed callus and. only 4,8 % of patients didn't have signs of consolidation. In the same terms at the fixation by bioinert plates adhesion of fracture didn't happen in 24 % of cases. Main mechanism of positive action of bioactive implants is connected with increase of calcium depot in blood and. decrease of markers of bone resorption in the first months after their installation.